2013
DOI: 10.1016/j.applanim.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping tight or hiding in fright? The welfare implications of different subtypes of inactivity in mink

Abstract: Effects of sub-optimal housing on inactivity vary across species and experiments, probably because inactivity is heterogeneous, reflecting both positive states (e.g. relaxation) and negative ones (e.g. fear). We therefore aimed to identify specific subtypes of inactivity that could indicate poor welfare in mink, by comparing their behaviour in enriched and non-enriched conditions (the former having been previously demonstrated to be highly preferred by mink and to enhance their welfare). We assessed this in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Power tests suggested that a minimum of approximately 30 mink per group were needed to detect a housing effect of equal size to that found in a previous study [59]. Faecal samples were collected from at least that number of mink per farm and treatment, resulting in a total sample of 188 females across all farms, representing all sister pairs housed in the same randomly chosen area of one shed per farm.…”
Section: Methodsmentioning
confidence: 99%
“…Power tests suggested that a minimum of approximately 30 mink per group were needed to detect a housing effect of equal size to that found in a previous study [59]. Faecal samples were collected from at least that number of mink per farm and treatment, resulting in a total sample of 188 females across all farms, representing all sister pairs housed in the same randomly chosen area of one shed per farm.…”
Section: Methodsmentioning
confidence: 99%
“…Meagher et al. () came to the same result that minks with no access to a second cage had higher FCM levels than minks with access to it.…”
Section: Discussionmentioning
confidence: 85%
“…Hansen et al., ; Svendsen et al., ; Meagher et al., ) mostly deals with female mink, which is why there is only few data on male mink (e.g. Meagher et al., ). The trial groups tested in our study contained both male and female animals.…”
Section: Discussionmentioning
confidence: 99%
“…Following the positioning change in the shed, the observational sampling increased to six days with three sets of 3 min focal observations each day to ensure adequate sampling of activity due to high levels of resting being observed (see Results). These observations were made standing as far back from the focal cages as possible (distance 1 m), a technique previously used successfully (Meagher et al 2013). The behaviors recorded were "activity" (walking, sniffing, eating, drinking, grooming etc.…”
Section: Behavioral Observations and Coordination Testingmentioning
confidence: 99%
“…The behaviors recorded were "activity" (walking, sniffing, eating, drinking, grooming etc. ), "resting" (lying still with eyes open or closed), "scrabbling" (scratching at a surface with front paws), and "locomotor stereotypy" (three or more replicates of pacing, bobbing, circling, routetracing; Meagher et al 2013). All observations took place in the morning after sunrise and prior to feeding.…”
Section: Behavioral Observations and Coordination Testingmentioning
confidence: 99%